2020
DOI: 10.1186/s12913-020-05949-1
|View full text |Cite
|
Sign up to set email alerts
|

Mental health professionals’ experiences with shared decision-making for patients with psychotic disorders: a qualitative study

Abstract: Background Shared decision-making (SDM) is a process whereby clinicians and patients work together to select treatments based on both the patient’s preferences and clinical evidence. Although patients with psychotic disorders want to participate more in decisions regarding their care, they have limited opportunities to do so because of various barriers. Knowing about health professionals’ experiences with SDM is important toward achieving successful implementation. The study aim was to describe and explore hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…In our study, the patients found that the professionals mainly presented information about a medicine when deciding on treatment. This is in line with a study that showed that health care professionals at the same CMHCs from which we recruited patients felt that SDM was about choosing antipsychotic medicine [ 29 ]. A previous study found that health care professionals sometimes decided not to inform patients about alternatives to the treatment they considered most relevant [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, the patients found that the professionals mainly presented information about a medicine when deciding on treatment. This is in line with a study that showed that health care professionals at the same CMHCs from which we recruited patients felt that SDM was about choosing antipsychotic medicine [ 29 ]. A previous study found that health care professionals sometimes decided not to inform patients about alternatives to the treatment they considered most relevant [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is interesting in light of another study of the same CMHCs as those included in this study. That study found that health professionals felt that informing patients about their health situation was an important aspect of SDM [ 29 ]. This may mean that patients and professionals at the same CMHCs have different experiences of the degree to which information is provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shared decision‐making in mental health settings remains limited, and focused on discussions about medications, with psychosocial approaches frequently presented as complimentary to medication rather than an alternative (Haugom et al . 2020). Additionally, clinicians’ low expectations of consumers’ ability to engage in shared decision‐making act as a further barrier (Dawson et al .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Poor service user involvement is also reflected in a study of mental health professionals' experiences with shared decision-making with service users with psychotic disorders, concluding that shared decision-making is practiced to only a limited extent with this group. 11 Involuntary medication has been found to be a particularly problematic form of coercion in service users' experience. 10 The majority of admitted service users in mental health care are treated with medication.…”
Section: Introductionmentioning
confidence: 99%